Serotyping of Toxoplasma gondii Infection Using Peptide Membrane Arrays - Arranz-Solís, David; Cordeiro, Cynthia; Young, Lucy H.; Dardé, Marie Laure; Commodaro, Alessandra G.; Grigg, Michael E.; Saeij, Jeroen P. J. (Frontiers in Cellular and Infection Microbiology, 2019)
The intracellular parasite Toxoplasma gondii can cause chronic infections in most warm-blooded animals, including humans. In the USA, strains belonging to four different Toxoplasma clonal lineages (types 1, 2, 3 and 12) are commonly isolated, whereas strains not belonging to these lineages are predominant in other continents such as South America. Strain type plays a pivotal role in determining the severity of Toxoplasma infection. Therefore, it is epidemiologically relevant to develop a non-invasive and inexpensive method for determining the strain type in Toxoplasma infections and to correlate the genotype with disease outcome. Serological typing is based on the fact that many host antibodies are raised against immunodominant parasite proteins that are highly polymorphic between strains. However, current serological assays can only reliably distinguish type 2 from non-type 2 infections. To improve these assays, mouse, rabbit and human infection serum were reacted against 950 peptides from 62 different polymorphic Toxoplasma proteins by using cellulose membrane peptide arrays. This allowed us to identify the most antigenic peptides and to pinpoint the most relevant polymorphisms that determine strain specificity. Our results confirm the utility of previously described peptides and identify novel peptides that improve and increase the specificity of the assay. In addition, a large number of novel proteins showed potential to be used for Toxoplasma diagnosis. Among these, peptides derived from several rhoptry, dense granule and surface proteins represented promising candidates that may be used in future experiments to improve Toxoplasma serotyping. Moreover, a redesigned version of the published GRA7 typing peptide performed better and specifically distinguished type 3 from non-type 3 infections in sera from mice, rabbits and humans.